Real-Time Water Level Monitoring and Early Warning Alarm System (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Awareness is a great factor in keeping someone safe and ready for any situation, most especially during calamities. Knowing when a certain event will happen and knowing its risk will make someone react accordingly to save lives and avoid considerable damages. The researchers proposed the development of Real-time Water Level Monitoring and Early Warning Alarm System. The system can monitor the water level through an ultrasonic sensor and will calculate the estimated time before the runoff occurs. The processed data will be displayed to the LCD monitor attached to the device and will send SMS messages to the selected individuals. When the risk is critical or the runoff has already happened, the beacon light and the siren horn will send a signal for a possible action that can be applied. The system has a power backup system in case of power interruption. The researcher used the waterfall method to develop the system. It is a method that defines several consecutive phases that must be completed before moving from one phase to the other. The process can be endlessly repeated until each phase was perfected. The phases of this method are Requirement Analysis, System Design, Implementation, Testing, Deployment, and Maintenance. Using a stopwatch timer, the researchers monitored the water level until it reached the runoff point where the water will spill out. The test showed that it will take 16 min and 38s before the demonstration platform will experience runoff. This test was conducted without the system installed. The system test showed that it will take 18 min and 57 s before the possible runoff of the demonstration platform in the presence of sensor devices where the possible changes in the water behavior happened the real-time water level monitoring and early warning alarm system showed accuracy because it can measure the changes in the flow rate of the water. This system can also send a notification after the data was been processed.
Keywords: real-time monitoring